6B4T in China: a case of Inter-Asian feminist knowledge negotiation and contestation through translation - Cheng Xiaoyi Y (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Previous researches exploring transcultural feminist knowledge transfer by means of translation pay little attention to translation flows in Asian countries. This study demonstrates what happened when a Korean radical feminist movement, 4B/6B4T, was exported to China through translation in an online environment. The Korean practitioners of 4B/6B4T have adopted several commitments, which have also travelled to China. The manner in which one of these commitments - 비돕비 (bidopbi, those who exercise 4 or 6B help those who exercise 4 or 6B) - should be translated into Chinese became a matter of controversy on Chinese social media. This study applies the sociological narrative theory to probe this translation debate and its embedded narratives. Moreover, the article employs the notions of fidelity and infidelity to discuss feminist activism in the context of translating 6B4T's commitments as a whole. The study considers feminist knowledge translation as a form of re-narration and intellectual activism that can be used to consciously strengthen the ideological agendas of feminist individuals. It argues that translation activism, when carried out in a feminist activist context via social media, can be understood as generative; it is enacted through the dynamic process of negotiating the mediators' narrative affinities.